Nongqawuse's Prophecies Revisited: Centring the Religious Experience - Slingers, Joshua (Department of Historical Studies, 2023)
This study examines the role played by traditional Xhosa religious belief and experience in the Xhosa Cattle-Killing Movement of 1856-57. Using a range of primary and secondary historical sources, this study focuses on the period between 1856 and 1857 where many of the amaXhosa slaughtered their cattle and ceased agricultural production. This study centres the work of South African historians in the analysis of the Cattle-Killing Movement and the prophecies of Nongqawuse. The study is framed by the conception of the movement as inherently religious in character and form. As such, certain elements of African and Xhosa religious beliefs form an important part of this study. The role of ancestors within Xhosa religious life, the spirits known as the ‘River People', the function of cattle in ritual sacrifice and the role of prophets and diviners in Xhosa life are all important in understanding the events of the Cattle-Killing Movement. Themes of rebirth and renewal are present within the prophecies and the wider movement. This study will argue that the religious aspects of the Cattle-Killing Movement have been given insufficient attention by materialists. This study seeks to address the problem of historians, and other scholars, studying the Cattle-Killing in disciplinary silos, favouring certain contributing factors while dismissing others. The prophecies of Nongqawuse were believed by the numerous participants because its content drew on past religious and mythological narratives that the Xhosa were familiar with and due to the adverse material circumstances of the mid-19th century. It will be shown that the Cattle-Killing Movement was determined by the lung sickness epidemic, other materialist and structuralist causes. However, just as importantly, it was determined by the religious beliefs and experiences of the believers.